Programa de pesquisa em monitoração ambiental: perspectivas e considerações metodológicas para uma agenda de desenvolvimento - Jaime Sadao Yamassaki Bastos (2010)
This study analyses the evolution of research on environmental scanning in Brazil and proposes a thematic research agenda. Despite the increasing volume of scientific literature in Information Science about environmental scanning, it has been possible to notice difficultiesregarding the generation and consolidation of scientific knowledge in this field in Brazil. This study investigated the issue by examining the relationships between theoretical development and the methodological directions that have characterized the practice of research in this area.Based on the analysis of Brazilian scientific literature about this topic, this study highlights the characteristics and the methods used, as well as theconsequences for the evolution of the field. It also presents a comprehensive analysis of the need for theory construction, as well as the challenges of such process. The relevance of the study regards the epistemological debate about production and nature of knowledge, trends and opportunities for development of models, methods, paradigms and theories applied to this field in Brazil. The discussion of such issues leads to the proposition of a thematic research agenda, aiming to support the consolidation of research programs.